The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.triboint.2018.03.034
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis and optimization of surface textures for a tilting pad thrust bearing

Abstract: A B S T R A C TA numerical model based on the Reynolds equation to study textured tilting pad thrust bearings considering massconserving cavitation and thermal effects is presented. A non-uniform and adaptive finite volume method is utilized and two methods are compared and selected regarding their efficiency in handling discontinuities; specifically placing additional nodes closely around discontinuities and directly incorporating discontinuities in the discrete system. Multithreading is applied to improve th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 22 publications
0
44
0
Order By: Relevance
“…Texture shape and size play a very important role in improving the bearing performance [55]. Many texture shapes like square [56][57][58]73], circular [59][60][61], elliptical [54,62,63], circumferential grooved [64,134], radial grooved [64][65][66] as shown in Fig. 7 are used to improve thrust bearing performance.…”
Section: Slider Bearing With Surface Texturingmentioning
confidence: 99%
“…Texture shape and size play a very important role in improving the bearing performance [55]. Many texture shapes like square [56][57][58]73], circular [59][60][61], elliptical [54,62,63], circumferential grooved [64,134], radial grooved [64][65][66] as shown in Fig. 7 are used to improve thrust bearing performance.…”
Section: Slider Bearing With Surface Texturingmentioning
confidence: 99%
“…Many other researchers focused on parametric studies, in particular for the analysis of surface textures. Since the early works of Etsion and coworkers [3,7] the parametric approach has been the widely used for the optimization of textures in several kind of application, such as 1D slider bearings [8,9], 2D slider bearings [10], Piston-Liner Contacts [11,12], thrust bearings [13] and pin-on-disc tribometers [14]. In some cases, the optimization of surface texture for 1D slider bearings has been also performed by means of analyt-ical solutions [15,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang studied the friction force of surface texture parallel sliders with different morphologies, and found that the hydrodynamic lubrication performance of circular textures is better with a lower friction coefficient [14]. Gropper analyzed the performance of bearing with variation of texture area and textured depth on surface determining that the optimum texture depth should be slightly less than the minimum film thickness of unreformed bearing, and that there existed an optimum texture depth and density with low friction existed [15]. Wang conducted research on texture density, and discovered that the friction force reduced favorably with a texture density of 5%~13%.…”
Section: Introductionmentioning
confidence: 99%